Alternativas a la laïcité: para un conocimiento menos augusto de la cultura europea y de su dimensión cristiana = Alternatives to laïcité : for a less august knowledge of European culture and its Christian dimension - Diotavelli, Luca (Ciencias sociales y religión, 2010)
This paper argues that secularity (laïcité) is just one among solutions provided by modernity in order to think and to manage the separation between religious and political powers. Taking in account for such a plurality of solutions reveals itself dramatically useful at a moment when laïcité regimes are dealing with a deep crisis and a “coming back of religion” based explanation of that crisis is spread but fragile if not inconsistent. (2.) Adopting a more sophisticated framework, than that implied by the classic secularisation’s theories, (3.) and particularly that proposed by Niklas Luhmann, laïcité regimes’ crisis appears depending primarily on state crisis. In fact, the laïcité is part of the state’s ideology and laïcité institutions are part of the state’s polity. (4.) On the contrary, working within stateless societies, religious freedom regimes deliver a real functional alternative in a situation characterised by laïcité regimes crisis. To this alternative are came back many Christian traditions, and particularly the Catholic one, who had been the birthplace of religious freedom.